(untitled) (Journal of Universal Science Research, 2023)
Lighting control is an extremely pressing task in the modern world. On the one hand, poor lighting leads to reduced safety, including injuries and deaths. On the other hand, excessive lighting leads to excess energy waste, which should be avoided. This article describes the development of a lighting control module based on Arduino Mega. The article provides a selection of the necessary equipment, and a block diagram of the proposed device is also created. A 3D model of the device case was developed, and the case was also printed on a 3D printer. The assembly of the developed lighting control module is proposed.